IMPROVING THE QUALITY OF FAITH THROUGH WORSHIP PACKAGE SHARING ACTIVITIES IN THE FRAMEWORK OF WELCOME THE HOLY MONTH OF RAMADHAN MAJELIS TA’LIM NURUL IMAN WITH DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK, KABUPATEN KUBU RAYA: PENINGKATAN KUALITAS IMAN MELALUI KEGIATAN BERBAGI PAKET IBADAH DALAM RANGKA MENYAMBUT BULAN SUCI RAMADHAN KERJASAMA MAJELIS TA’LIM NURUL IMAN BERSAMA DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN KUBU RAYA - Lia Nurina (STAI Al Fithrah Press, 2023)
Majelis Ta’lim is a place or institution for education, training, and teaching and learning activities in studying, exploring, and understanding Islamic religious knowledge and as a forum for carrying out various activities that provide benefit to the congregation and the surrounding community. The committee of the Majelis Ta’lim has new innovations on how the Majelis Ta’lim Nurul Iman is growing. The arrival of the holy month of Ramadan 1444 Hijriah, where this month of Ramadan is considered the most blessed month to share with one another. So then the Majelis Ta’lim Nurul Iman collaborated with Dinas Pemberdayaan Perempuan dan Perlindungan to carry out sharing activities, especially for mothers and children in the Limbung Village environment. The community service activity with the theme of sharing together was carried out on March 20 2023. On this occasion, the taklim assembly Nurul Iman gave mukenah and robes to mothers in need with the hope that this gift would be very useful so that mothers who received assistance could be more diligently again carrying out his prayer services, providing assistance in the form of clothing, food and health which are daily needs such as clothing, prayer equipment and food with the aim of not only helping his physical growth but his soul and mind. The sharing activity with others that has been carried out is expected to provide benefits for mothers in the Dusun Mulyorejo Desa Limbung Kecamatan Sungai Raya Kabupaten Kubu Raya.